Milk yield of some goat breeds in Croatia - Boro Mioč; Vesna Pavić; Zdravko Barać; Zvonimir Prpić; Ivan Vnučec (Mljekarstvo)
In Croatia, goats are primarily bred for meat production. However, for the past twenty years the interest in goat milk production was based on imported breeds such as Alpine-French, Saanen and German Improved Fawn goat. The purpose of this paper is to establish litter size of the principal goat breeds in Croatia and the indicators related to milk yield and chemical composition. The largest average litter size has been determined on the German Improved Fawn (1.72), then with the Boer (1.54), the Saanen (1.53) and the Croatian coloured goat (1.51), while the Alpine-French goat was the smallest (1.31). The longest lactation period (259 days) has been determined on the Alpine-French goat, while the largest milk yield during lactation (724.4 kg) and the largest milk fat yield (20.16 kg) and protein yield (18.64 kg) have been determined on the Saanen goat. However, it has been established that the Alpine-French goat milk has the highest average fat content (3.55 %), while the German Improved Fawn’s milk has the highest protein content (3.23 %). The Saanen goat had the longest milking period (222 days) and the shortest suckling period (32 days), while the Alpine-French and the German Improved Fawn had the longest suckling period (51 and 45 days, respectively). The lowest quantity of milk during the suckling period (102.97 kg, i.e. 14 %) was suckled by Saanen kids, while the Alpine-French (122.08 kg, i.e. 22 %) and the German Improved Fawn kids suckled the greatest quantity (116.31 kg, i.e. 22 %).